1998
DOI: 10.1159/000012713
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age and Origin of Human Milk Influence Total Lipid and Fatty Acid Contents

Abstract: The human milk composition may be influenced by several factors, such as gestational age or genetic characteristics and dietary habits of different populations. To analyze the total lipid and fatty acid contents of human milk, we have conducted two studies, one on mothers who had delivered preterm and term newborns and another on mothers from two different sociocultural backgrounds (Spain and Panama). The total lipid content (g/100 g wet weight) was significantly higher in term (2.76 ± 0.66; mean ± SD) than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
38
3
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 31 publications
11
38
3
2
Order By: Relevance
“…Our result for MUFA in colostrum was in the middle of the European Range (ER 39.11 -45.19%;Fidler & Koletzko, 2000) and agree with the figures in other Spanish (Rueda et al, 1998;Pita et al, 1985) studies of 42.00 and 41.46%, respectively. We found similar MUFA percentages in a German study (Genzel-Boroviczeny et al, 1997), but the percentage of oleic acid was only 32.16%, whereas in our study oleic acid accounted for 38.83%.…”
Section: Fatty Acid Composition Of Human Milksupporting
confidence: 92%
See 2 more Smart Citations
“…Our result for MUFA in colostrum was in the middle of the European Range (ER 39.11 -45.19%;Fidler & Koletzko, 2000) and agree with the figures in other Spanish (Rueda et al, 1998;Pita et al, 1985) studies of 42.00 and 41.46%, respectively. We found similar MUFA percentages in a German study (Genzel-Boroviczeny et al, 1997), but the percentage of oleic acid was only 32.16%, whereas in our study oleic acid accounted for 38.83%.…”
Section: Fatty Acid Composition Of Human Milksupporting
confidence: 92%
“…Our results confirm the trend in two Spanish studies reported with an interval of 13 y (Rueda et al, 1998;Pita et al, 1985). The latter study showed a considerably lower linolenic acid content (0.41 vs 1.09%), accompanied by a remarkable increase of the LA=LnA ratio, from 19.1 (1985) to 27.5 (1998).…”
Section: Fatty Acid Composition Of Human Milksupporting
confidence: 92%
See 1 more Smart Citation
“…O conteúdo total de lipídeos e a composição de ácidos graxos do leite humano são variáveis, como pode ser comprovado em diversos estudos 2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Mandel et al 16 estimaram o conteúdo de gordura do leite humano pelo método do crematócrito, que consiste na mensuração das quantidades de creme e de soro após a centrifugação de capilares contendo uma alíquota de leite humano.…”
Section: F a T O R E S Q U E M O D U L A M A C O M P O S I ç ã O D O unclassified
“…The human milk composition may be influenced by several factors, such as gestational age, genetic characteristics, dietary habits, nutritional and socioeconomic state of mothers, duration of lactation and length of gestation (Rueda et al, 1998;Beijers & Schaafsma, 1996;Bunker et al, 1996;Yeh et al, 1996). Dietary (milk) lipids are very important for the normal growth and development of infants (Ambartsumyan, 1998;Giovannini et al, 1991).…”
Section: Introductionmentioning
confidence: 99%